ChemInform Abstract: Microwaves in Heterocyclic Chemistry. Issue 32 (18th July 2013) - Bazureau, Jean Pierre; Paquin, Ludovic; Carrie, Daniel; L'Helgoual'ch, Jean Martial; Guiheneuf, Solene; Coulibaly, Karime Wacothon; Burgy, Guillaume; Komaty, Sarah; Limanton, Emmanuelle
Abstract Review: 166 refs.